2015
DOI: 10.1530/erc-15-0263
|View full text |Cite
|
Sign up to set email alerts
|

The mammary stem cell hierarchy: a looking glass into heterogeneous breast cancer landscapes

Abstract: The mammary gland is a dynamic organ that undergoes extensive morphogenesis during the different stages of embryonic development, puberty, estrus, pregnancy, lactation and involution. Systemic and local cues underlie this constant tissue remodeling and act by eliciting an intricate pattern of responses in the mammary epithelial and stromal cells. Decades of studies utilizing methods such as transplantation and lineage tracing have identified a complex hierarchy of mammary stem cells, progenitors and differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 128 publications
(169 reference statements)
1
45
0
Order By: Relevance
“…Early studies of ductal outgrowth during organogenesis and androgenmediated regeneration showed that cellular proliferation is highly enriched at ductal tips, suggesting a distal location for prostate epithelial progenitors (Sugimura et al, 1986a,b). Notably, a distal localization is consistent with the distribution of stem/progenitor cells during ductal outgrowth of tissues such as the lung and mammary gland (Hogan et al, 2014;Sreekumar et al, 2015). Furthermore, expression of Nkx3.1 is elevated in ductal tips (Kruithof-de Julio et al, 2013), and a role for Nkx3.1 in progenitor specification and maintenance has been suggested by the ductal morphogenesis defects in Nkx3.1 null mutants as well as by the stem cell properties of luminal Nkx3.1-expressing cells (termed CARNs; castration-resistant Nkx3.1-expressing cells) in the regressed adult prostate (Bhatia-Gaur et al, 1999;Wang et al, 2009).…”
Section: Lineage Specification During Organogenesis Homeostasis and supporting
confidence: 53%
“…Early studies of ductal outgrowth during organogenesis and androgenmediated regeneration showed that cellular proliferation is highly enriched at ductal tips, suggesting a distal location for prostate epithelial progenitors (Sugimura et al, 1986a,b). Notably, a distal localization is consistent with the distribution of stem/progenitor cells during ductal outgrowth of tissues such as the lung and mammary gland (Hogan et al, 2014;Sreekumar et al, 2015). Furthermore, expression of Nkx3.1 is elevated in ductal tips (Kruithof-de Julio et al, 2013), and a role for Nkx3.1 in progenitor specification and maintenance has been suggested by the ductal morphogenesis defects in Nkx3.1 null mutants as well as by the stem cell properties of luminal Nkx3.1-expressing cells (termed CARNs; castration-resistant Nkx3.1-expressing cells) in the regressed adult prostate (Bhatia-Gaur et al, 1999;Wang et al, 2009).…”
Section: Lineage Specification During Organogenesis Homeostasis and supporting
confidence: 53%
“…As pointed out in other reviews, [4, 32] clonal evolution and hierarchical heterogeneity are not mutually exclusive models, and are likely to be concurrently exerting their respective influences within breast tumors (Figure 3). Implicit in this view of multiple breast cancer subtypes is the potential for interactions between the disparate disease types, as applies generally to intra-tumoral heterogeneity (i.e.…”
Section: Cooperativity Between Distinct Disease Subtypes In Breast Tumentioning
confidence: 80%
“…In fact, there are reports of more differentiated luminal breast cancer cells exhibiting equal tumor initiating capacity as basal/stem-like breast cancer cells [13, 19]. Further insights and elucidation of the normal mammary hierarchy, which are extensively covered by these reviews [20, 21, 32], will be vital to the understanding of various distinct CSC populations in breast tumors. Additionally, comprehension of the intrinsic and niche factors that govern each of the normal mammary stem/progenitor cell states may shed light on the vulnerabilities of distinct CSC populations.…”
Section: Cancer Stem Cells: a Source Of Non-genetic Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations